Using Wavelet Approach to Analyze Exchange Rate Exposure Puzzle: Evidence from Tehran Stock Exchange - Abdolmajid Jalaee; Amir Habibdoost (فصلنامه پژوهش‌های اقتصادی ایران, 2012)
In this paper we examine the relationship between exchange rate movements and stock return (Firm value), which is known as Exchange Rate Exposure, using a Time-Scale approach in different sectors of Tehran Stock Exchange (TSE). In this regard, we decompose the exchange rate percent changes and stock return over the period 1998-2008, as well as the period 2004-2008(according to data limitation), by applying MODWT method; moreover, we run wavelet base regression and analyze wavelet variance, covariance and correlation. Results reveals that exchange rate exposure not only differs from one sector to other sector but it also differs through time scales. Hence, this issue should be considered as a multi scales problem.